Drosophila Dynein Intermediate Chain Gene, Dic61B, Is Required for Spermatogenesis - Fatima, Roshan (Public Library of Science, 2011)
This study reports the identification and characterization of a novel gene, Dic61B, required for male fertility in Drosophila. Complementation mapping of a novel male sterile mutation, ms21, isolated in our lab revealed it to be allelic to CG7051 at 61B1 cytogenetic region, since two piggyBac insertion alleles, CG7051(c05439) and CG7051(f07138) failed to complement. CG7051 putatively encodes a Dynein intermediate chain. All three mutants, ms21, CG7051(c05439) and CG7051(f07138), exhibited absolute recessive male sterility with abnormally coiled sperm axonemes causing faulty sperm individualization as revealed by Phalloidin staining in Don Juan-GFP background. Sequencing of PCR amplicons uncovered two point mutations in ms21 allele and confirmed the piggyBac insertions in CG7051(c05439) and CG7051(f07138) alleles to be in 5′UTR and 4(th) exon of CG7051 respectively, excision of which reverted the male sterility. In situ hybridization to polytene chromosomes demonstrated CG7051 to be a single copy gene. RT-PCR of testis RNA revealed defective splicing of the CG7051 transcripts in mutants. Interestingly, expression of cytoplasmic dynein intermediate chain, α, β, γ tubulins and α-spectrin was normal in mutants while ultra structural studies revealed defects in the assembly of sperm axonemes. Bioinformatics further highlighted the homology of CG7051 to axonemal dynein intermediate chain of various organisms, including DNAI1 of humans, mutations in which lead to male sterility due to immotile sperms. Based on these observations we conclude that CG7051 encodes a novel axonemal dynein intermediate chain essential for male fertility in Drosophila and rename it as Dic61B. This is the first axonemal Dic gene of Drosophila to be characterized at molecular level and shown to be required for spermatogenesis.